UJI EFEKTIVITAS EKSTRAK RIMPANG LENGKUAS MERAH (Alpinia Purpurata K. Schum) TERHADAP Candida albicans - Siti Juariah; Tri Setia Ningrum; Eli Yusrita (Jurusan Teknologi Laboratorium Medis, Poltekkes Kemenkes Denpasar, 2023)
Background: Infectious diseases are diseases caused by the entry and breeding of microorganisms, namely bacteria, viruses, fungi, prions and protozoa into the body, causing organ damage. Candidiasis is a disease caused by the fungus Candida albicans, commonly found in the skin, mucous membranes and digestive tract. Infection control usually uses antibiotics, but continuous use can lead to resistance to microbes, the use of alternative materials is needed. Red galangal is one type of spice that has been widely used as a phytopharmaceutical product or a product that utilizes vegetable resources as a source of medicinal ingredients. Aim:The purpose of the research was to determine the effect of red galangalrhizome extract on the growth of Candida albicans. Methods:The methods used are experimental and disc diffusion method. Based on the results of the study, it can be seen that there is an inhibitory response seen from the difference in the distance of theinhibition zone between the negative control and several other concentrations. Resulsts:The results of the measurement of the inhibition of Candida albicans using concentrations of 10%, 20%, 40%, and 60% respectively 11.3 mm, 13 mm, 13.3 mm, 14.3 mm. positive control (ketoconazole) formed an inhibition zone diameter of 8.6 mm while negative control did not form an inhibition zone. Conclusion:Based on the results of the study, it can be concluded that the red galangal rhizome extract (Alpinia purpurata K.Schum) has the ability as an antifungal against the growth of Candida albicans.